Towards Agility In Design In Global Component- Based Development. - KOTLARSKY, JULIA; OSHRI, ILAN; KUMAR, KULDEEP; VAN HILLEGERSBERG, JOS (Communications of the ACM, 2008)
The article discusses component-based development (CBD) methodologies, examining the manner in which component-based (CB) architecture will enable CB software development teams to create products with more agility. The study analyzes two CB project teams, located around the world, exploring how each team handled inter-site coordination and challenges to their communication. Other topics include building software systems by integrating pre-existing software components, shorter time-to-market periods, and reduced development costs.